2015
DOI: 10.1002/ange.201504192
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Photoswitching of a Spin‐Crossover Molecular Complex in the Solid State at Room Temperature

Abstract: Spin-crossover metal complexes are highly promising magnetic molecular switches for prospective moleculebased devices.T he spin-crossover molecular photoswitches developed so far operate either at very low temperatures or in the liquid phase,which hinders practical applications.Herein, we present am olecular spin-crossover iron(II) complex that can be switched between paramagnetic high-spin and diamagnetic low-spin states with light at room temperature in the solid state.T he reversible photoswitching is induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…DAE photoswitches based on π-linkers that are part of an aromatic ring (such as 4, Scheme 1b) are highly desirable for the functionalization of complex molecular materials, [15][16][17][18] but remain scarcely investigated. [19][20][21] Aromatic DAEs containing phenanthrene 13,22 and phenanthroline 14,15,23 moieties, which were developed by Walko and Feringa (5) 13 or Yam et al (6), 14 were shown to operate under similar conditions to conventional DAE switches (Scheme 1c), while effectively mimicking olefinic systems in accordance with Clar's rule of π-sextets, leaving the central core of these systems with lower aromatic delocalization of the electron density (Scheme 1c). [24][25][26] In contrast, the phenyl-DAE systems are not reported to photocyclize (Scheme 1b), 12 possibly due to the fact that this system is more aromatic and therefore 'resistant' to photocyclization.…”
Section: Methodsmentioning
confidence: 99%
“…DAE photoswitches based on π-linkers that are part of an aromatic ring (such as 4, Scheme 1b) are highly desirable for the functionalization of complex molecular materials, [15][16][17][18] but remain scarcely investigated. [19][20][21] Aromatic DAEs containing phenanthrene 13,22 and phenanthroline 14,15,23 moieties, which were developed by Walko and Feringa (5) 13 or Yam et al (6), 14 were shown to operate under similar conditions to conventional DAE switches (Scheme 1c), while effectively mimicking olefinic systems in accordance with Clar's rule of π-sextets, leaving the central core of these systems with lower aromatic delocalization of the electron density (Scheme 1c). [24][25][26] In contrast, the phenyl-DAE systems are not reported to photocyclize (Scheme 1b), 12 possibly due to the fact that this system is more aromatic and therefore 'resistant' to photocyclization.…”
Section: Methodsmentioning
confidence: 99%
“…Recently Khusniyarov et al have used a phenanthroline ligand functionalized by a photochromic diarylethene moiety in a bis(pyrazolyl)borate Fe(II) complex ( Figure 6). Under UV-irradiation, the open HS form is reversibly converted (about 40%) to a LS closed form [49,50]. In parallel, Oshio et al studied similar compounds and showed bidirectional spin-state switching by LIESST and reverse-LIESST in the solid state and in butyronitrile solution [51].…”
Section: Spin State Change By Ligand Field Strength Modulationmentioning
confidence: 99%
“…This system exhibits a wide thermal hysteresis in the spin transition, above room temperature. 18 While X-ray absorption spectroscopy (XAS) is frequently used to probe changes in electronic structure, 17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] X-ray core level photoemission at the Fe 2p core has also been used to probe the molecular spin crossover, 27,[41][42][43][44][45] but only in a limited manner. So far, data from X-ray photoemission spectroscopy (XPS) has not been adequate to make a detailed comparison with magnetometry or XAS, nor has the XPS data been sufficient to abstract a critical spin crossover transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…One is the light induced activation of the low spin to high spin state switch, i.e. light-induced excited spin-state trapping (LIESST), 4,26,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] and soft X-ray-induced excited spin state trapping (SOXIESST). 26 These light and X-ray induced spin state changes occur at temperatures well below the spin crossover temperature (T 1/2 ) where the low spin state should be dominant.…”
Section: Introductionmentioning
confidence: 99%